Magic light / Edy Samrizal Mat Harun and Hasnan Che Ismail - Mat Harun, Edy Samrizal; Che Ismail, Hasnan (2003)
This project entitled magic light. It functions to decorative light. Different dancing colour pattern are produced by using this circuit since LED can produced different colours. I he most useful of this proiect is to change the night ambience to be looking more interesting with colorful light especially at the expo, party and night club. The advantage of this project is used less power than other lamp. Therefore, the cost of electricity will decrease